Szenosphäre & Szenotopie: Künstlerische Forschungen zur Raumwahrnehmung und -struktur der Szenografie - Prangen, Ruth (transcript, 2017)
Scenosphere and scenotopia - research on the atmosphere, spatial perception, topology and spatial structure of scenography that operates in the space between discourse and artistic practice.